Institute of Medicine Levels of Weight Gain in the Obese Diabetic Patient: Do Maternal and Neonatal Outcomes Differ? [27R]. (May 2016) - Mehra, Suwan; Rice, Jim; Goldkamp, Jennifer; Gavard, Jeffery A.; Catanzaro, Rose; Artal, Raul
Abstract : INTRODUCTION: To determine the impact on adverse maternal and neonatal outcomes in the Obese Diabetic Patient, amongst different (IOM) levels of gestational weight gain. METHODS: This was a retrospective review of 161 obese women with GDM or DM2 age 18+. Predictability of gestational weight gain for adverse outcomes was examined for the greatest level of weight gain >20 lbs, 11–20 lbs in comparison to the least amount of weight gain <11 lbs using multiple logistic regression and chi square linear-by-linear test for trend. RESULTS: Using a regression model with Gain <11 as the reference, gestational weight gain is significantly associated with an increase in Cesarean delivery (CD), P =.027 and Preeclampsia, P =.028. No significance was seen for LGA, P =.215 and CHTN, P =.338. The adverse outcomes across the greatest and least gestational weight gain was examined by the test for trend as follows preeclampsia, P =.005, CD, P =.085, LGA, P =.216 and CHTN, P =.384. 2% of women with a weight gain of <11 lbs developed preeclampsia, compared to the 12% and 19% in the 11–20 lbs and >20 lbs groups respectively. CONCLUSION: The fetal growth patterns and duration of NICU stay and the maternal glucose variability in the obese pregnant population do not differ amongst various IOM weight gain categories. However, obese women with a weight gain more than 20 pounds have a 9 fold increased risk to develop preeclampsia and increase in cesarean delivery rates compared to women with less than an 11 pound weight gain.